Analysis of the Cooling Load of the Air Conditioning System on the 1st Floor of the Dian Nusantara University Building Using the CLTD Method - Wa Ode Fanesya Taqwim; Komarudin Komarudin (Greenation International Journal of Engineering Science, 2025)
In Indonesia's tropical climate, educational buildings such as Dian Nusantara University face thermal comfort challenges due to high temperatures and intense solar radiation, necessitating accurate cooling load analysis for AC system optimization. This study aims to calculate the total cooling load on the first floor using a descriptive quantitative approach with the ASHRAE-based CLTD method, through measurements of building dimensions, occupants, equipment, and the local climate of Cibubur. The results indicate a total load of 53.88 kW (15.3 TR), dominated by wall envelopes (32.0%), glass (21.1%), and occupants (17.1%), while the installed AC capacity of 70 kW is 30% oversized in aggregate but undercapacity in some rooms. The conclusions emphasize the need to adjust AC capacity per room and the combination of split and cassette AC types for energy efficiency; implications include operational cost savings and improved thermal comfort in tropical buildings.